Why a diversified portfolio should include African assets - Paul Alagidede; Theodore Panagiotidis; Xu Zhang (TÜSİAD-Koç University Economic Research Forum, 2010)
We employ parametric and non-parametric cointegration to investigate the extent of integration between African stock markets and the rest of the world. Long-run correlation estimates imply very low association between the two. The two distinct cointegration approaches confirm the latter through recursive estimation. The implication is that global market movements may have little impact on Africa. However,we argue that including African assets in a mean variance portfolio could be beneficial to international investors.
Keywords: C22; C52; G10; 330; Correlation; Long-run correlation; Cointegration; Non-parametric cointegration; African Stock Markets; Kapitalmarktliberalisierung; Marktintegration; Börsenkurs; Kointegration; Nichtparametrisches Verfahren; Afrika